A study on the continuance participation in on-line communities with social commerce perspective - Hajli, N.; Shanmugam, M.; Powell, P.; Love, Peter (Elsevier Inc., 2014)
This study investigates the constructs and related theories that drive continuance participation in on-line communities from their intention and behaviour perspectives. The research uses theories of 'social support' and 'planned behaviour' to propose a research model that drives continuance participation in on-line communities in Malaysia. The model reveals that the constructs perceived behavioural control, subjective norms, and attitude from the Theory of Planned Behaviour juxtaposed with social support constructs and a perceived value construct significantly influences on-line communities' continuance participation intention and behaviour. Using PLS-SEM to analyse data gathered in Malaysia, the research demonstrates that users' continuance participation is dependent on their intention and behaviour. The study also contributes to the understanding of individuals' use of on-line communities in the social commerce era.